Down and out or up and in?: in search of Latin America's elusive middle class - Cruces, Guillermo Antonio (2009)
The main motivation of this paper is to discuss the existing empirical implementations of the middle class in the applied literature and to derive a definition based on sound principles from distributional analysis. The document also provides comparative results on the extent and evolution of middle classes from a variety of existing definitions since the early 1990s for six Latin American countries. To avoid some of the arbitrariness of traditional measures, we propose an endogenous definition based on the polarization literature. Other socioeconomic features of the middle classes in the region according to different definitions are described and discussed. The results are also presented for the lower and upper classes.